Catechins as Antimicrobial Agents and Their Contribution to Cosmetics - Soraya Ratnawulan Mita; Nurul Inaya Muhtar; Sri Agung Fitri Kusuma; Sriwidodo Sriwidodo; Ryan Proxy Hendrawan (Cosmetics, 2025)
Natural ingredients are an important source of bioactive compounds. Among these bioactive compounds, polyphenols are the most interesting because of their health benefits. Catechins are a class of polyphenol compounds that exhibit a range of activities, with applications in the pharmaceutical and cosmetic industries. These include antimicrobial, antioxidant, anti-inflammatory, and other therapeutic effects. In cosmetic formulations, catechins can be used as anti-acne agents. Reducing the particle size of catechins affects several of their physicochemical properties and can also increase their absorption rates and solubility. This article discusses the physicochemical properties of catechins and their potential applications as antimicrobial agents.